Implementasi Pengelolaan Dana Bergulir di Pasar Rakyat Imogiri Kabupaten Bantul - Harun Al Rosyd; Syakdiah; Oktiva Anggraini (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2023)
Implementation of revolving fund management as a follow-up to Bantul Regent Regulation No. 47 of 2017 concerning Mechanisms for Disbursement, Distribution and Revolving Fund Refunds for Market Traders. The purpose of the study was to determine the implementation of revolving fund management in Rakyat Imogiri market, Bantul Regency and to find out the smoothness of beneficiaries, returns and monitoring of effective, transparent and accountable evaluation of revolving funds. The type of research used is descriptive qualitative. The implementation of revolving fund management in Rakyat Imogiri market is seen from (1) The achievement of applications and verification through the ability of officers in achieving tasks. (2) Compliance with procedures through conformity of rules and loan mechanisms by traders. (3) Satisfaction is seen from the side of the traders who use it and the officers who carry it out quite well. Matters that affect the implementation of revolving fund management (1) Beneficiaries know the loan application requirements and the verification team works according to the rules. (2) Merchants receive benefits with an easy process and in accordance with applicable regulations. (3) Monitoring and evaluation there are a number of traders carrying out their installment obligations that are not on time and there are loans that come to a standstill due to the death of the borrower